Costly Inflation Misperceptions - Thomas A. Eife; Stephan Meier (University of Heidelberg, Department of Economics, 2007)
One of the consequences of the euro changeover in 2002 was that for a period of several years people considerably overestimated actual inflation. The goal of this paper is to study whether misperceptions of this kind may have real effects, that is, whether they induce people to alter their behaviour. We also discuss the question how far the euro changeover and the ensuing discussion about price stability contributed to the recession that followed the changeover. Looking at the German restaurant sector, we find that people's misperceptions can have significant negative effects. The contraction this sector experienced in the months after the changeover was too pronounced to be explained by normal business cycle movements. We provide a discussion about the causes of these misperceptions and how to avoid them in future changeovers.
Keywords: D12; E21; C22; 330; euro changeover; perceived inflation; Währungsumstellung; Euro; Inflationserwartung; Wahrnehmung; Gastronomie; Branchenkrise; Deutschland